Analisis Pengaruh Perubahan Beban Terhadap Biaya Bahan Bakar Pembangkitan Pada PLTU Barru - La Ode Musa; Musrady Mulyadi; Muh. Fachriyadi Hastira; Hasniaty Hasniaty (Politeknik Negeri Ujung Pandang, 2021)
The effect of changes in load on the cost of fuel generation at PLTU Barru is analyzed using the economic dispatch method to determine the characteristics of input-output and incremental fuel costs. Based on the results of the analysis, it is known that the effect of changes in load on the cost of fuel generation at PLTU Barru tends to be directly proportional, where the higher the load generated, the higher the costs incurred. As in June, to produce 33.85 MW of power the total cost is Rp. 457,687,187.47/hour required. Likewise, if the power at an average load of 33.85 MW increases by 1 MWh it will result in an increase in costs of Rp. 13,306,061.24/MWh, but in certain circumstances such as in November with a power of 29.83 MW it will produce the total cost is quite low at Rp. 337,356,512,63/hour. This situation is caused by fuel consumption in November only amounted to 3029.61 T/h.